Flood hazard mapping for the gonbad chi region, Iran. Issue 1 (24th February 2017) - Sepehri, Mehdi; Ildoromi, Ali Reza; Malekinezhad, Hossein; Hosseini, Seyed Zeynalabedin; Talebi, Ali; Goodarzi, Saba
Abstract : Flood hazard (FH) can be considered as one of the most serious threats mainly in areas and countries where other natural hazards hardly occur. This paper presents a simple approach to urban FH assessment in regions where the primary data are scarce. The objective of this study is to develop a geographic information system-aided urban FH zoning of the study area (in Iran), by applying multicriteria decision analysis and fuzzy analysis. In this process, the research methodology focused on the analysis of the variables controlling water routing. The model incorporated four parameters: distance to the drainage channels, topography (topographic wetness index), infiltration and cover type. The results demonstrated that most floods occur near the discharge channels and in the lower parts of the study area.